1976
DOI: 10.2134/agronj1976.00021962006800050019x
|View full text |Cite
|
Sign up to set email alerts
|

Time and Rate of Fertilizer Application for Seeded Warm‐season and Bluegrass Pastures. I. Yield and Botanical Composition1

Abstract: Field studies were initiated in 1971 and continued through 1974 to evaluate the influence of time and rate of fertilizer application for both seeded warm‐season and bluegrass (Poa pratensis L.) pastures. The warm‐season pastures consisted of a mixture of big bluestem (Andropogon gerardi Vitman), switchgrass (Panicum virgatum L.), indiangrass (Sorghastrum nutans L.) and sideoats grama (Bouteloua curtipendula L.). Prior studies had shown that fertilization would increase production of several forage species. Yet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
1
1

Year Published

1985
1985
2014
2014

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 14 publications
1
17
1
1
Order By: Relevance
“…Similar increases in switchgrass forage yield in response to P fertilization have been reported elsewhere [19][20][21] and also in greenhouse studies [23]. A 22% increase in forage yield in response to 90 kg Pha −1 was reported for four warm-season grasses: bermudagrass (C. dactylon L.), weeping lovegrass [Eragrostis curvula (Schreb.)…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Similar increases in switchgrass forage yield in response to P fertilization have been reported elsewhere [19][20][21] and also in greenhouse studies [23]. A 22% increase in forage yield in response to 90 kg Pha −1 was reported for four warm-season grasses: bermudagrass (C. dactylon L.), weeping lovegrass [Eragrostis curvula (Schreb.)…”
Section: Discussionsupporting
confidence: 82%
“…Despite presence of data showing P fertilizer response of switchgrass grown for forage in low P soils [19][20][21][22] and in greenhouse studies [23], there is a paucity of information on the effects of P on biomass yields of switchgrass harvested after frost for bioenergy. Therefore, experiments were conducted from 2008 to 2010 at two locations in southern Oklahoma to evaluate how P fertilizer rates affect switchgrass on P-deficient soils in the Great Plains.…”
Section: Introductionmentioning
confidence: 99%
“…The purpose of the fertilizer treatments was to stimulate the dominant vegetation so that yields of a cool-season system could be compared to yields of the warm-season system. The warm-season plots (atrazine-treated) and the cool-season plots (untreated) were each fertilized at the optimum time (Rehm et al 1976). The field plot design was a split plot.…”
Section: Materinks and Methodsmentioning
confidence: 99%
“…28 However, research in Nebraska suggested switchgrass may respond to applied P if P availability in the soil is low. 29,30 Th e response of switchgrass to other mineral elements is largely uninvestigated and remains a major research need in most areas where switchgrass potentially will be grown as a bioenergy crop.…”
Section: Establishing and Managing Switchgrassmentioning
confidence: 99%